2013
DOI: 10.3233/jad-2012-121357
|View full text |Cite
|
Sign up to set email alerts
|

Elevated MARK2-Dependent Phosphorylation of Tau in Alzheimer's Disease

Abstract: The appearance of neurofibrillary tangles (NFT), one of the major hallmarks of Alzheimer's disease (AD), is most likely caused by inappropriate phosphorylation and/or dephosphorylation of tau, eventually leading to the accumulation of NFTs. Enhanced phosphorylation of tau on Ser(262) is detected early in the course of the disease and may have a role in the formation of tangles. Several kinases such as microtubule-affinity regulating kinase (MARK), protein kinase A, calcium calmodulin kinase II, and checkpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Ser262 of tau is the most important residue phosphorylated by MARK2 for MT dynamics 53, 54 and that phosphorylation of this residue is enhanced in AD, which may have a role in tangle formation. 55, 56 The interaction between MARK2 and tau has also been investigated extensively. 56 We demonstrated that the protein expression and stability of the S262A tau mutant, which inhibits the interaction between MARK2 and tau, were significantly increased by DAPK1, similar to that of WT tau, suggesting that DAPK1-enhanced tau protein stability is independent of MARK proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ser262 of tau is the most important residue phosphorylated by MARK2 for MT dynamics 53, 54 and that phosphorylation of this residue is enhanced in AD, which may have a role in tangle formation. 55, 56 The interaction between MARK2 and tau has also been investigated extensively. 56 We demonstrated that the protein expression and stability of the S262A tau mutant, which inhibits the interaction between MARK2 and tau, were significantly increased by DAPK1, similar to that of WT tau, suggesting that DAPK1-enhanced tau protein stability is independent of MARK proteins.…”
Section: Discussionmentioning
confidence: 99%
“…55, 56 The interaction between MARK2 and tau has also been investigated extensively. 56 We demonstrated that the protein expression and stability of the S262A tau mutant, which inhibits the interaction between MARK2 and tau, were significantly increased by DAPK1, similar to that of WT tau, suggesting that DAPK1-enhanced tau protein stability is independent of MARK proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation event is a prerequisite for the action of downstream kinases, including glycogen synthase kinase-3 and cyclin-dependent kinase 5 (Cdk5) to phosphorylate several other sites and generate disease-associated phospho-epitopes (43). The augmented interactions between MARK2 and Tau in AD brain sections suggest that MARK2 may play an important role in the early phosphorylation of Tau in AD, possibly qualifying as a therapeutic target for intervention to prevent disease progression (44,45). Impairment of the cAMP/PKA/CREB pathway may contribute to the learning/memory deficits in AD (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…A panspecific phosphorylation antibody could also be used in pair with the anti-PDGFRb antibody for imaging the phosphorylation of PDGFRb [34]. The methodology has been further applied to investigate the MARK2-dependent serine phosphorylation of Tau in NIH-3T3 cells [35], and the tyrosine phosphorylation of ABL, SHC, ERK2 and PI3K in response to kinase or phosphatase inhibitor treatment in K562 cells [36].…”
Section: Phosphorylationmentioning
confidence: 99%